2021
DOI: 10.1007/s10649-021-10078-5
|View full text |Cite
|
Sign up to set email alerts
|

Social class inequalities in attitudes towards mathematics and achievement in mathematics cross generations: a quantitative Bourdieusian analysis

Abstract: Drawing on Bourdieu’s theory of social and cultural reproduction, this article utilizes the conceptual tools of habitus and cultural capital to examine intergenerational inequalities in attitudes towards mathematics and mathematics learning in three secondary schools in England. Data from 1079 students aged 14–16 included mathematics achievement, survey measures of attitudes towards mathematics, perceived parental attitudes towards mathematics, newly developed scales for cultural capital and habitus, and socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…Similarly, Quaye and Pomeroy (2022) in their study of 1079 students' aged 14-16 in three secondary schools in England found a very strong relationship between students' attitudes, perceptions and, interest toward mathematics, and students' perceptions of their parents' attitudes toward mathematics. The finding of their study suggested that students' attitude needs to be positive to learn mathematics.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Similarly, Quaye and Pomeroy (2022) in their study of 1079 students' aged 14-16 in three secondary schools in England found a very strong relationship between students' attitudes, perceptions and, interest toward mathematics, and students' perceptions of their parents' attitudes toward mathematics. The finding of their study suggested that students' attitude needs to be positive to learn mathematics.…”
Section: Discussionmentioning
confidence: 88%
“…At the secondary level, mathematics is considered as a core subject (Quaye & Pomeroy, 2022). The market value placed on high‐level mathematical skills needed for certain commercial, technological and scientific roles makes mathematics subject as core than other subjects (Quaye & Pomeroy, 2022). Mathematics subject is a core academic skill that has been receiving increasing attention (Vostanis et al, 2021) at which students need to achieve better results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Practical applications of abstract mathematical content can arouse interest in the content covered and this interest can extend to other courses. Future work can investigate how interest is socially constructed, that is, the development of ilussio (Bourdieu, 1994), which could explain the difference between looking at mathematics at the individual and group level (Jorgensen et al, 2014;Quaye & Pomeroy, 2022). In addition, the most frequent use of modeling in various contexts and content can not only maintain interest, but also improve it.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in our modeling context, a student may be interested in modeling by witnessing the hard work of colleagues and begins to try to reach the target, that is, to produce the model. Some researchers have applied Bourdieu's (1994) ideas in the field of mathematics education (Jorgensen et al, 2014) including in some aspects of the attitude towards mathematics (Quaye & Pomeroy, 2022).…”
Section: Interestmentioning
confidence: 99%